PENGARUH PENAMBAHAN ZAT PENGATUR TUMBUH BAP (BENZYL AMINO PURINE) DAN 2,4-D (2,4-DICHLOROPHENOXYACETICACID) TERHADAP PEMBENTUKAN PLANLET MELON (Cucumismelo) VARIETAS MAI119 - Toharah, Nining Intan; Jekti, Dwi Soelistya Dyah; Zulkifli, Lalu (Bioscientist : Jurnal Ilmiah Biologi, 2015)
This study aims to determine the concentration of growth regulators BAP and 2,4-D which have the highest effect in stimulating the formation of shoots and roots melon plants (Cucumis melo) Mai 119 variety. The callus leaves of seedlings were used as a source explant. Completely randomized design (CRD) was used in this research. Media used on shoot induction was MS medium added with several concentration of BAP (0 mg/L, 1 mg/L, 2 mg/L, 3 mg/L) and 2,4-D (0 mg/L, 1 mg/L, 2 mg/L, 3 mg/L) either alone or in a combination of both. Media used in the formation of roots were MS medium added with 2,4-D at a several concentration of 0 mg/L, 1 mg/L, 2 mg/L, and 3 mg/L. Parameters measured were the time appearing of shoots, number of shoots, time appearing of roots, and the number of roots. Parameters measured were the time appearing of shoots and number of shoots using descriptive test. Anova followed by Tukey's test was used in the analyse time appearing of roots. In the parameter number of roots using Kruskal Wallis test followed by Mann-Whitney test. The results showed that there were differences in the effect of growth regulators on the shoots and roots formation. The fastest shoot induction was obtained in the media 3 mg/L BAP+1 mg/L 2,4-D with the highest number of shoots contained in the medium at a concentration of 3 mg/L BAP + 1 mg/L 2,4-D and 2 mg/L BAP+1 mg/L 2,4-D. The fastest root induction was obtained in media 0 mg/L 2,4-D, 1 mg/L 2,4-D, and 2 mg/L 2,4-D. The highest number of roots were obtained in media with 0 mg/L 2,4-D and 1 mg/L 2,4-D.